Methyl Methacrylate and Alpha-Methyl Styrene: New Strategy for Synthesis of Bloc Copolymers for Use in Potential Biomedical Applications Generated by an Ecologic Catalyst Called Maghnite (Algerian MMT) - Moulkheir Ayat; Mohamed Belbachir; Abdelkader Rahmouni (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
A new model for synthesis of the plastics, block copolymers were prepared from methyl methacrylate (MMA) and alpha-methyl styrene (α-MS) by cationic copolymerization in the presence of a new and efficient catalyst of “Maghnite-Na” at 0 °C in bulk. In this paper, the copolymerization of α-MS and MMA was induced in heterogeneous phase catalyzed by Maghnite-Na was investigated under suitable conditions. The “Maghnite-Na” is a montmorillonite sheet silicate clay, with exchanged sodium cations to produce Na-Montmorillonite (Na+-MMT) obtained from Tlemcen, Algeria, was investigated to remove heavy metal ion from wastewater as an efficient catalyst for cationic polymerization of many vinylic and heterocyclic monomers. The synthesized copolymer were characterized by Nuclear Magnetic Resonance (NMR-1H, NMR-13C), FT-IR spectroscopy, Differential Scanning Calorimetry (DSC), and Gel Permeation Chromatography (GPC) to elucidate structural characteristics and thermal properties of the resulting copolymers. The structure compositions of “MMT”, “H+-MMT” and “Na+-MMT” have been developed. The effect of the MMA/α-MS molar ratio on the rate of copolymerization, the amount of catalyst, temperature and time of copolymerization on yield of copolymers was studied. The yield of copolymerization depends on the amount of Na+-MMT used and the reaction time. The kinetic studies indicated that the polymerization rate is first order with respect to monomer concentration. A possible mechanism of this cationic polymerization is discussed based on the results of the 1H-NMR Spectroscopic analysis of these model reactions. A cationic mechanism for the reaction studies showed that monomer was inserted into the growing chains.